Castles and the Anglo-Norman world : proceedings of a conference held at Norwich Castle in 2012 - Davies, John A.; Davies, John A.; Riley, Angela; Riley, Angela; Levesque, Jean-Marie; Levesque, Jean-Marie; Lapiche, Charlotte; Lapiche, Charlotte (Oxbow Books, 2016)
Preface / George Nobbs -- Introducing Norman connections / John A. Davies, Angela Riley, Jean-Marie Levesque and Charlotte Lapiche -- Foreword: Living in the twelfth-century cross-channel empire / David Bates -- Part I. The Norman Connections castles -- Norwich Castle / Elizabeth Popescu -- "Traces of the original disposition of the whole" : excavated evidence for the construction of Norwich Castle keep / Brian Ayers -- The shifting structure of Norwich Castle keep, 1096 to c. 1230 / T.A. Heslop -- Colchester Castle : "Some tyme stronge and statelye, as the ruynes do shewe" / Peter Berridge -- Rochester Castle / Marc Morris -- Le Château de Falaise : bilan de 150 ans de restaurations dans plus de 1000 ans d'histoire / Charlotte Lapiche and Benoît Panozzo -- Le Château de Caen / Jean-Marie Levesque et Pascal Leroux -- The Great Hall of the Dukes of Normandy in the castle at Caen / Edward Impey and John McNeill -- Part II. The castles in context -- Châteaux et résidences princières dans la Tapisserie de Bayeux / Pierre Bouet -- Visible from afar? : the setting of the Anglo-Norman donjon / Jon Gregory and Robert Liddiard -- Some thoughts on the use of the Anglo-Norman donjon / Pamela Marshall -- Part III. Recent archaeological research -- Recent research on the White Tower : reconstructing and dating the Norman building / Roland B. Harris -- Castle heritage (10th-13th centuries) in Lower Normandy and the current state of archaeological research / François Fichet de Clairfontaine -- Recent excavations at Caen Castle (2005-2014) : medieval forges and Renaissance stable / Bénédicte Guillot -- Part IV. Presenting the sites -- Le Château de Falaise (Calvados) : état des connaissances sur l'évolution du site castral du dixième siècle au treizième siècle / François Fichet de Clairfontaine, Joseph Mastrolorenzo et Richard Brown -- The question of site enhancement in rural contexts : examples of projects managed by the Calvados Departmental Council (Conseil générayl du Calvados), Lower Normandy / Nicola Coulthard -- The evolution of capitals in early post-Conquest architecture as evidence for the completion date of the White Tower / John Crook -- Anglo-Norman elite objects from castle and countryside / Steven Ashley.